Determinant Factors for Community Participation in Dutungan Island of Barru Regency - Ilham Junaid (Jurnal Kawistara, 2021)
Understanding determinant factors in community participation is essential in encouraging community participation in tourism activities. However, community participation studies mainly focused on identifying community participation issues and reasons to advocate community participation. This research aims at 1) exploring factors that affect community participation in tourism, and 2) proposing strategies to encourage active participation by the local community. This paper employs a qualitative methodology conducted in 2019. The research reveals that community participation around Dutungan Island has three categories: supportive participation, micro business-based creation participation and passive participation. The determinant factors for community participation include; 1) private management of tourism attraction; 2) lack of collective awareness by the local community, and 3) lack of skills and knowledge in tourism. This paper proposes the importance of implementing communitybased tourism village; strengthening cooperation between the owner or manager of Dutungan Island and the local community; and optimising Dutungan Island management’s role to help the local people who reside the village. Dutungan Island’s manager should be able to share profit to help the local people through social programs that may include training for the local people and providing investment for micro business. This paper provides insight into how to encourage community participation through the role of different stakeholders, including the island and the local community.